Low hazard small-scale synthesis and chemical analysis of high purity nitroglycerine (NG) - Contini, Alessandro E.; Flood, Nathan; McAteer, Daniel; Mai, Nathalie; Akhavan, Jacqueline (Royal Society of Chemistry (RSC), 2015)
A previously reported two-phase (99.5% fuming nitric acid/dichloromethane) batch method to prepare high purity 1,2,3-propanetriyl trinitrate (nitroglycerine, NG) was evaluated, simplified and adapted specifically for low hazard small-scale synthesis. The purity of the product, as determined by NMR spectroscopy, HPLC and IR spectroscopic analysis was found to be greater than 99%. The quick synthetic method is highly recommended when small amounts of highly pure NG are required for analytical and related purposes in the absence of a microreactor.